IDENTIFIKASI KUAT TEKAN BATUAN PADA DESA RABAK DAN SEKITARNYA, KECAMATAN RUMPIN, KABUPATEN BOGOR, JAWA BARAT - Muhammad Kresna Atthariqh; Mira Meirawaty; Muhammmad Adimas Amri (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
. To determine the compressive strength of rocks, a Point Load test is needed where this method is commonly used in the world of rock mechanics in order to determine the point of rock damage to the maximum load that can be accepted by the rock. To find out how strong the rock can accept the load it receives, the rock's breaking point is the benchmark. The purpose of this study was to identify the compressive strength of Andesite, Tufa sandstone, Sandstone, and Claystone when under pressure. This research was conducted at the Geological Engineering Laboratory, Trisakti University, Jakarta. Rock sampling was carried out in the village of Rabak and its surroundings, Rumpin District, Bogor Regency, West Java. After carrying out the Point Load test, the results of the compressive strength of Andesite are 16 Kn / cm2, Sandstone 12.5 Kn / cm2 (in the direction of layer) & 11.11 Kn / cm2 (opposite layer), tuffaceous sandstone 8 Kn / cm2 (in the direction of layer) & 6.25 Kn/cm2 (opposite layer) , and Claystone 3.33 Kn/cm2. Based on the measurement results, a rock strength map in the study area can be made.